2001
DOI: 10.1128/aem.67.12.5608-5613.2001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Detachment of Cell Clusters from Mature Mixed-Species Biofilms

Abstract: Detachment from biofilms is an important consideration in the dissemination of infection and the contamination of industrial systems but is the least-studied biofilm process. By using digital time-lapse microscopy and biofilm flow cells, we visualized localized growth and detachment of discrete cell clusters in mature mixed-species biofilms growing under steady conditions in turbulent flow in situ. The detaching biomass ranged from single cells to an aggregate with a diameter of approximately 500 m. Direct evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
202
3
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(221 citation statements)
references
References 17 publications
11
202
3
5
Order By: Relevance
“…This mixed-species biofilm has previously been shown to be reproducible with respect to structure and viable cell counts (Jackson et al, 2001;Stoodley et al, 2001). In addition, these three species are commonly found in soil habitats and are reported to coexist in metalworking fluids, where the growth of P. protegens is a prerequisite for the growth of P. aeruginosa and K. pneumoniae (Chazal, 1995).…”
Section: Introductionmentioning
confidence: 85%
“…This mixed-species biofilm has previously been shown to be reproducible with respect to structure and viable cell counts (Jackson et al, 2001;Stoodley et al, 2001). In addition, these three species are commonly found in soil habitats and are reported to coexist in metalworking fluids, where the growth of P. protegens is a prerequisite for the growth of P. aeruginosa and K. pneumoniae (Chazal, 1995).…”
Section: Introductionmentioning
confidence: 85%
“…A biofilm is a surfaceassociated three dimensional consortia of microbial communities, surrounded by a matrix of protective biopolymers, macromolecular debris, sediment and precipitate, making it a highly complex mechanical, compliant, and viscoelastic structure. Biofilms can also be highly heterogeneous consisting of mixed populations of bacteria, fungi, protozoa [112] with interspersed pores and channels. Biofilms exhibit enormous resistance to external stress factors, with exopolysaccharides (EPS) contributing to their overall mechanical stability and enabling them to withstand external forces.…”
Section: Biofilms Contribute To Viscoelasticitymentioning
confidence: 99%
“…A decade ago it was demonstrated that biofilms are effectively viscoelastic, a property that plays a major role in the various stages of biofilm growth [109,112,[114][115][116][117]. Biofilms, all of which exhibit classic viscoelastic behaviours [109,115,116,118,119], can grow in a wide variety of environments including laboratory conditions, under flow and even in hot springs, demonstrating their ability to absorb elevated changes in shear stresses.…”
Section: Biofilms Contribute To Viscoelasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Release of microbial cells from the biofilm structures or from the surface (Stoodley et al 2001a); the process of active release is physiologically controlled. Separate cells and small clusters are released more often, but large pieces are also released; the latter constitute a health hazard regarding the infectious dose (Stoodley et al 2001b). The released bacteria or their clusters drif within the liquid environment or are attached to damp semi-finished products and ready-made foodstuffs and can become sources of microbial contamination of other surfaces (Zottola & Sasahara 1994) or the products of both animal and vegetable origins (Rayner et al 2004).…”
Section: Biofilm Formationmentioning
confidence: 99%